RuO2 Nanorods on Electrospun Carbon Nanofibers for Supercapacitors - Jeon, Sohyun; Jeong, Ji Hwan; Yoo, Hyomin; Yu, Hak Ki; Kim, Bo Hye; Kim, Myung Hwa (ACS Applied Nano Materials, 2020)
RuO2 nanorods on electrospun carbon nanofibers were simply grown by precipitation and recrystallization methods for studying their capacitive behaviors for supercapacitor applications. Recrystallization by heat treatment is carefully performed at various temperatures: 180, 220, and 300 °C. Under optimal growth conditions, application of RuO2-carbon nanofibers annealed at 220 °C with a very low loading concentration of Ru as the electrode material in a KOH aqueous electrolyte leads to a good capacitance capability of 188 F g-1 at a current density of 1 mA cm-2 and a high energy density of 22-15 W h kg-1 in the power density range of 400-4000 W kg-1 for supercapacitor applications. The capacitance of RuO2-carbon nanofibers after 3000 cycles also maintains approximately 93% of its initial value at a discharge current density of 1 mA cm-2. The excellent electrochemical performance of RuO2-carbon nanofibers is mainly attributed to their large surface area with many mesopores as well as their electroactive functional sites, which have the appropriate degree of crystallinity. Therefore, a larger mesopore volume and low-dimensional RuO2 nanorods on carbon nanofibers are beneficial for low internal resistance, leading to ion charge diffusion and charge storage in the bulk of amorphous material.
Keywords: Aqueous electrolyte; Degree of crystallinity; Discharge current density; Electrochemical performance; Electrospun carbon nanofibers; High energy densities; Internal resistance; Supercapacitor application; crystal phase of RuO2; electrospun carbon nanofiber; microstructure; recrystallization temperature; supercapacitor